NARCISSISM NARRATIVE TEXT ANALYSIS OF SEMIOTIC DISCLOSURE ANNUAL REPORT PT MERDEKA COPPER GOLD TBK - Anak Agung Gde Satia Utama; Ika Putri Elviana (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
The purpose of this study is to analyze the phenomenon of narcissism on the case study in a business operation project of PT Merdeka Copper Gold Tbk. in Tumpang Pitu Banyuwangi. In addition, as a company that uses narcissism narrative text for PT Merdeka Copper Gold Tbk. The primary data is from the annual report of PT Merdeka Copper Gold Tbk. in 2015 - 2016 analyzed using semiotic analysis. The results of this study indicate that PT Merdeka Copper Gold Tbk. used narcissism of narrative text that is persuasive to stakeholders with positive performance, especially in the delivery of CSR with exaggeration in the annual report. It is a communicative management action to gain legitimacy, and to create a positive image to stakeholders.